The concept of administrative efforts in resolving village apparatus disputes in Ptun (Study decision number: 25/g/2019/ptun. mtr jo. number: 199/b/2019/pt.tun.sby) - Jumawal Jumawal; Siti Hasanah; Firzhal Arzhi Jiwantara (Institute Of computer Science (IOCS), 2024)
The purpose of this research is to find out and understand the concept of administrative efforts to resolve Village Apparatus disputes in PTUN related to Decision Number: 25/G/2019/PTUN.Mtr Jo Decision Number: 199/B/2019/PT.TUN.Sby. The research method used in this research is a type of normative legal research, with a statutory approach, conceptual approach and case approach. The technique for collecting and retrieving legal materials used in this research is library research. The data obtained is analyzed using qualitative data analysis, where the presentation of qualitative data can be in the form of narrative text (in the form of field notes), then the data will be organized and arranged in a relationship pattern which will be easier to understand. From the research results the following conclusions can be drawn: 1) Concept administrative efforts understood and implemented by the Mataram State Administrative Court (PTUN) and the Surabaya State Administrative Court (PTTUN) in Decision Number: 25/G/2019/PTUN.MTR Jo. Number: 199/B/2019/PT.TUN.SBY regarding dispute resolution for Village Officials in South Setanggor Village which turns out to be different from each other. The difference lies in whether the implementation of administrative efforts in resolving Village Apparatus disputes is mandatory or optional; 2) Since the publication of Law no. 30 of 2014 concerning Government Administration, gives rise to the paradigm that the regulation of administrative efforts requires the integration of the administrative justice system with administrative efforts.